DNA methylation of imprinted loci of autosomal chromosomes and IGF2 is not affected in Parkinson's disease patients' peripheral blood mononuclear cells. (4th March 2017) - Kaut, Oliver; Sharma, Amit; Schmitt, Ina; Wüllner, Ullrich
Abstract: Objective : Genomic imprinting is an epigenetic phenomenon that results in differential expression of alleles, depending on their parental origin. The functional significance of DNA methylation in genomic imprinting has been widely investigated, and to date, approximately 100 imprinted genes have been identified in humans. Methods : To investigate whether the methylation status of these 'known' imprinting genes was associated with Parkinson's disease (PD), we analyzed the methylation profiles of all 'known' imprinted genes using the Illumina 450K methylation chip. Samples were derived from mononuclear blood cells of 17 male Parkinson's disease patients vs. 21 healthy male individuals and 12 discordant MZ twin pairs. Results : None of the annotated autosomal genes show changes in DNA methylation between PD individuals and healthy individuals. We further refined our analysis by evaluating the DNA methylation status of the maternally imprinted human gene encoding insulin-like growth factor 2 ( IGF2) using bisulfite sequencing PCR (BSP) of DNA derived from 15 PD patients and 9 controls, taking into consideration different dosages of L-dopa. Conclusion : Our results demonstrated that methylation of IGF2 in PD patients was neither influenced by the dosage of L-dopa treatment nor by the disease itself. Thus, loss or disruption of imprinting in autosomal chromosomes does not seem to be relevant for the pathogenesis of the disease.